e-CSq: Landscape planning and maintenance in health facilities / Norsyazlin Mohd Rosli ... [et al.] - Mohd Rosli, Norsyazlin; Borhan, Ruwaidah; Muhammad Soffian, Nur Shaffiqa (2024)
Database management demands a creative and innovative approach for landscape planning and maintenance in health facilities. Health facilities require efficient database management of spatial and attribute data in landscape planning and maintenance, particularly in the mapping of trees that can contribute to environmental benefits in health facilities. Health facilities integrate gardens and landscaping for the purpose of healing, treatment, restoration, and rehabilitation. The use of Geographic Information Systems (GIS) enhances landscape planning and saves the results in present information systems for future reference, as part of the component in environmental information or decision support systems. In addition, GIS can be utilized to save data for organizing inventories, conducting scientific analyses, describing aims, describing scenarios or alternative futures, and for planning. The aim of this innovation is to develop a database management for landscape planning to create tree mapping. The database will be used by landscape contractors and maintenance professionals to identify trees exhibiting high levels of carbon sequestration, thus improving a sustainable environment in health facilities.